Developing TaRL Audio Strategies Integrated with Bima Local Wisdom for Visual Impairment Students - Ilyas Ilyas; Ahyar Ahyar; Mafrur Udif Nofaizzi; Syarifudin Syarifudin; Arif Rahman Hakim; Muslim Muslim (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2025)
Listening literacy is a fundamental skill that plays a crucial role in the cognitive development and communication skills of blind students. For blind students, listening literacy is the primary means of learning and understanding various social and cultural contexts in their environment. Their reliance on hearing makes audio media a crucial learning instrument. However, the availability of appropriate audio learning media for blind students is still very limited. In Bima, there is no audio media for children's stories containing Bima local wisdom for learning for blind students. Consequently, the Research and Development Agency of the Ministry of Education and Culture noted that more than 60% of blind elementary school students have not been able to achieve the minimum standard in listening skills for audio-based narrative and descriptive texts. This study aims to produce audio media for children's stories based on Teaching at the Right Level (TaRL) containing the Bima local wisdom of Ngaha Aina Ngoho as a means of improving listening literacy for blind students. The method used is the 4D development model (define, design, develop, disseminate). The define stage reveals the limitations of contextual media that suit students' needs. In the design stage, a story script was prepared with three levels of difficulty based on the results of the TaRL assessment. The development stage showed validation results from six experts with an average score of 90.7% (very feasible category), and a limited trial on five students obtained an average N-Gain of 0.67 (medium-high category). In the dissemination stage, the media received a positive response from teachers because it was considered practical, relevant, and interesting. This audio media for children's stories containing the local wisdom of Bima Ngaha Aina Ngoho will certainly be very useful as a learning medium for blind students in listening literacy.